Analisis Gambaran Peta Perjalanan Pasien di Pelayanan Rawat Jalan RS Kanker “Dharmais” Tahun 2014 - Majid, Fitri Amalia Nur (UI Scholars Hub, 2014)
The focus of this study is about outpatient journey of “Dharmais” Cancer Hospital in 2014 with purposes to find the unit with highest variation of patient journey and to analize the cause of the variation. This research is cross-sectional qualitative. The results of this research show that APJ Instalation is the unit with the highest variation of patient journey, and the causing factors are softtare of the computer supporting the service, human resource, infrastructure, and service procedures. The researcher found out that high variation of patient journey will reduce the quality of the service.